2019
DOI: 10.1111/acer.14131
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure Impairs AMPK Signaling and Phagocytosis in Human Alveolar Macrophages: Role of Ethanol Metabolism

Abstract: Background: Chronic alcohol consumption impairs alveolar macrophage's (AM) function and increases risk for developing lung infection and pneumonia. However, the mechanism and metabolic basis of alcohol-induced AM dysfunction leading to lung infection are not well defined, but may include altered ethanol (EtOH) and reactive oxygen species metabolism and cellular energetics. Therefore, oxidative stress, endoplasmic reticulum (ER) stress, the formation of fatty acid ethyl esters [FAEEs, nonoxidative metabolites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
4
16
0
Order By: Relevance
“…Extraction and analysis of FAEEs formed by hPACs treated with 1,2-13 C-EtOH in the presence/absence of AMPKα activator (AICAR) were performed as described previously [24]. Triglyceride content in hPACs treated with EtOH with/ without AICAR was measured using a triglyceride colorimetric assay kit as per manufacturer's instructions (Cat # 10010303, Cayman Chemical, Ann Arbor, MI).…”
Section: Faee and Triglyceride Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction and analysis of FAEEs formed by hPACs treated with 1,2-13 C-EtOH in the presence/absence of AMPKα activator (AICAR) were performed as described previously [24]. Triglyceride content in hPACs treated with EtOH with/ without AICAR was measured using a triglyceride colorimetric assay kit as per manufacturer's instructions (Cat # 10010303, Cayman Chemical, Ann Arbor, MI).…”
Section: Faee and Triglyceride Analysesmentioning
confidence: 99%
“…AMPKα is a crucial regulator of energy metabolic homeostasis, and its inactivation plays a significant role in key cellular events that are involved in the pathogenesis of various diseases [23]. More recently, EtOH-induced AMPKα dysregulation has been linked to ER stress in alveolar macrophages and the liver [24,25]. However, the role of AMPKα in ER stress and its link towards the initiation and progression of ACP is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence suggests that dysregulation of unfolded protein response (UPR) induced by endoplasmic reticulum (ER) stress in acinar cells after chronic alcohol consumption promotes the development of pancreatitis (Lugea et al, 2017a; Pandol et al, 2010). On the other hand, dysregulation of AMP‐activated protein kinase (AMPKα), a major regulator of cellular metabolism and ER/oxidative stress (Kim et al, 2015; Steinberg & Kemp, 2009), plays a key role in the pathogenesis of various diseases, including EtOH‐related disorders (Chen et al, 2010; Kaphalia et al, 2019; Liangpunsakul et al, 2010; Shearn et al, 2014; Srinivasan et al, 2019). An underlying link between EtOH‐induced AMPKα inactivation and ER/oxidative stress in relation to pancreatic acinar cell injury, and its inflammatory responses and cellular bioenergetics could be key factors for the initiation of ACP (Srinivasan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In order to further interpret this gene module, we performed over-representation analysis on this gene set, which is analogous to GSEA and we found that, among these were gene sets relating to the unfolded protein response (UPR). This result is intriguing because the UPR has been associated with ethanol toxicity and withdrawal in other tissues 42 and other cell types including macrophages 43 but has not been identified in microglia in the central nervous system. Interestingly, Erickson and colleagues detected altered expression of a module involving response to unfolded protein in both cortical microglia and astrocytes in acutely intoxicated mice after CIE whereas we observed this module to be reduced in EtOH-0h animals compared to Air controls but increased after withdrawal 38 .…”
Section: Discussionmentioning
confidence: 98%